ISSUES OF STUDYING THE HISTORIOGRAPHY OF HERBS AND SPICES - Nargiza I. Karimova (Current Research Journal of History, 2022)
The first information about the use of herbs and spices dates back to more than 6000 BC. Trade in herbs and spices in Europe began about 1000 years ago and their price was equal to the value of gold [1]. At the beginning of the new millennium, a number of generalizing works by prominent foreign researchers were published on the study of the history of the trade in herbs and spices among the works of foreign scientists of the 20th century. It should be noted the monographs of J. Baker, A. Hermann, E. Schaefer [2], monographs of American and English scientists A. Giuliano, Y. Lerner and J. Tucker [3], as well as Chinese - Zhang Ji Ping and Liu Zhi Juan[4], in which an attempt was made to generalize how issues of studying the trade of herbs and spices on the Silk Road, as well as its history. However, these specialists, first of all, are Sinologists they paid more attention to the history of the Great Silk Road in the context of China’s international relations.